Keep Them Rocking at Home:: Thriving in Place - Boober, Becky (Maine Policy Review, 2015)
The Thriving in Place Initiative (TiP) described by Becky Hayes Boober aims to help people with chronic health conditions remain safely in their communities instead of being hospitalized or placed in residential care facilities. Funded by grants to communities from the Maine Health Access Foundation, TiP builds on and coordinates health care and supports already in a community.
Keywords: Maine; aging; Thriving in Place Initiative